Pengaruh Pemasaran Digital dan Ulasan Online terhadap Keputusan Pembelian Produk Skintific pada Marketplace Sociolla - Dila Irawati; Citra Savitri; Syifa Pramudita Faddila (Journal Of Business, Finance, and Economics (JBFE), 2022)
In this study, Sociolla is an online market application, Sociolla offers a variety of products such as the needs of mothers and children, fashion, make-up and skin care. This study aims to examine the influence of digital marketing, influencer marketing and online customer reviews on purchasing decisions of skintific products on the Sociolla marketplace. The objects used in this study are Sociolla e-commerce users. This research uses a quantitative approach with a survey method. The analysis used is Data Validity Test, Classical Assumption Test, Multiple Linear Regression Analysis and Hypothesis Testing. The population in this study were Management Students Batch 2019 at Buana Perjuangan University, Karawang. A sample of 100 respondents was taken based on a saturated sampling technique with the criteria of having/intention to buy Skintific products on the Sociolla marketplace. Based on the results of the research that has been done, the results show that digital marketing and online reviews have a positive and significant effect on purchasing decisions for Skintific products on the Sociolla marketplace for Management Students Class of 2019 at Buana Perjuangan University, both partially and simultaneously. Digital marketing and online reviews can explain the buying decision variables